Tools for HR Analytics ANALISA DI PT. KIMIA FARMA TBK - Malvin Agustino; Yulia Herman; Anggun Dea; Annisya Mega; Rezky Dwiham (Bajang Institute, 2023)
This study discusses the use of Tools for HR Analytics at PT. Kimia Farma Tbk, a leading pharmaceutical company in Indonesia. The aim is to analyze the implementation of these tools and the challenges faced. The study shows that the use of HR Analytics helps the company in analyzing HR data, making strategic decisions, improving HR processes efficiency, employee performance, and employee experience. However, the challenges include a lack of understanding of data analysis and the need for skilled human resources to operate HR Analytics tools. This research provides a deeper understanding of the use of HR Analytics technology in human resource management, which can be used for the development of more effective systems.